Assessing the Strength and Quality of Timber Construction in Masjid Kampung Patah Pedang and Masjid Kampung Parit Lapis Bangas Using Non-Destructive Testing - Ramali, Fathin Najihah; Adnan, Nor Azizah (Recent Trends in Civil Engineering and Built Environment, 2025)
In Malaysia, structural failures in constructions pose significant risks to the safety of occupants and incur substantial repair expenses for the community. This research focuses on two historical mosques, Kampung Parit Lapis Bangas and Jamek An Nur Kampung Patah Pedang, built in 1961 and 1950, respectively. These mosques exhibit damages such as cracking, termite infestation, and fungi growth, raising concerns about their structural integrity. This project aims to evaluate the modulus of elasticity (MoE) and assess the strength of timber used in the mentioned mosques through Ultrasonic Pulse Velocity (UPV) testing. Non-Destructive Testing (NDT) is employed in these mosques by utilizing UPV testing to evaluate the quality and strength of timber without compromising its integrity. There are 65 damages structures (column and beam) involved in this testing by using direct method for column and indirect method for roof beam. The MoE is calculated using the formula MoE = 0.899 MoEdyn, where MoEdyn = ρV2x10-6. Minimum MoE values for Chengal and Ponak wood are established as 14,000 MPa and 7,600 MPa, respectively based on Malaysia Standard. The analysis reveals significant differences in MoE values between the mosques due to variations in wood types, damage types, and structure heights. Kampung Parit Lapis Bangas Mosque, constructed with Chengal Wood (SG1), exhibits higher MoE values than Jamek An Nur Kampung Patah Pedang Mosque, which uses Ponak Wood (SG4). Three columns in Jamek An Nur Kampung Patah Pedang mosque show weakened conditions because these columns falling below the minimum MoE of 7,600 MPa. This study suggests to carry out treatment on the damaged structure such as injected treatment using epoxy resin and fungus control chemicals to minimize the damage and increase the strength of the wood.